White labour in black slave plantation society /and economy : a case study of indentured labour in seventeenth century Barbados - Beckles, Hilary MacDonald (1980)
This study was prompted by the need to fill a gap within the labour historiography of the English speaking West Indies. From the 1950s, the number of works dealing with Black and Asian indentured servitude have been rapidly increasing. In this upsurge of interest in West Indian history the study of white indentured servitude, the basis of the early plantation economy, remained largely unworked. This study attempts to evaluate the importance of white indentured labour to plantation development in Barbados, the most valuable colony within the English mercantile system of the seventeenth century. The use of indentured labour, which was recruited from England, Scotland, Wales and Ireland for commodity production in the first half of the century, provided the basis for the gradual transition to Black slavery. This process is analysed to show the development of the ideologies of race and colour, and their application to the division of labour in the West Indies. The transformation of the English institution of indentured servitude, with its pre-industrial, moral, paternalistic superstructure, into a market system of brutal servitude, is a central theme of the work. The contradictions of white labour in a Black slave economy and society, at the levels of ideology and entrepreneurial economic thinking, are analysed to show the failure of the white servants to entrenched themselves in the West Indies, either as peasants or as a proletariat. Finally, the study explores the West Indian dimension of the European labourers' experience in the New World, where the majority found a life more oppressive and fruitless than that which they had left behind.
HydraID: hull:5389 Hydra Discover Access Group: public EThOS identifer: 380801 ETD Collection: ETDHistory
Keywords: History; Slavery